Elucidating the proportion of CD4+ and CD8+ regulatory t-cells, associated Cytokines, and epstein-barr virus’ LMP1 Xhoi mutation in nasopharyngeal carcinoma - Irekeola, Ahmad Adebayo (2023)
Regulatory T-cells (Tregs) are thought to be involved in the immunopathogenesis of many cancers including nasopharyngeal carcinoma (NPC) which is known to be strongly associated with Epstein-Barr virus (EBV) infection. Loss of EBV latent membrane protein 1 (LMP1) XhoI restriction site has been suggested to define EBV strain associated with increased tumourigenicity. Despite the perceived roles of Tregs and EBV LMP1 XhoI mutation in cancers, their roles in the pathogenesis of NPC are yet to be fully elucidated. Hence, this study aims to elucidate the proportion of Tregs, associated cytokines, and LMP1 XhoI mutation in NPC in order to provide baseline and additional data to foster the strides of current and future immunotherapeutic approaches. Blood samples were collected from NPC patients (n=23) and healthy controls (n=23). Tissue biopsy was available for 7 of the NPC patients. Samples were assessed for Tregs (CD4+FoxP3+, CD4+CD25+FoxP3+, CD8+FoxP3+, and CD8+CD25+FoxP3+) using multicolour flow cytometry, and XhoI mutation using polymerase chain reaction. Tregs proliferation was determined by Ki67 expression, and ex vivo proliferation was assessed after culturing PBMCs with IL-2 and anti-CD3/CD28 mAbs. The expression levels of five cytokines (IL-2, IL-10, IL-6, TNF-α, and IFN-ƴ) were evaluated using multiplex bead analysis. Tregs were generally found to be elevated in NPC patients. XhoI mutation was detected in both patients (39%) and controls (30%). The correlation between clinicopathological features and the frequency of circulating Tregs in the patients revealed no significant correlation for both CD4+ and CD8+ Tregs, even though Tregs levels were fairly higher in patients with stage IV compared with stage II/III cancer. In comparison with unstimulated cells, both CD4+ and CD8+ Tregs proportion heightened following the ex vivo culture of PBMCs. CD4+ and CD8+ Tregs in the PBMCs obtained from healthy controls responded better to ex vivo stimulation compared with those from patients. Of the cytokines, significant expression levels were observed for plasma IL-10 and TNF-α in patients compared with controls. The concentration of IL-10 was significantly lower in patients (10.47 ± 16.17 versus 16.12 ± 33.38, p = 0.0157). Meanwhile, plasma levels of TNF-α were higher in patients (p <0.0001) and were found to correlate with CD4+ Tregs in controls but not in patients. Correlation between IL-2 and CD8+CD25+FoxP3+ (r = -0.4670, p = 0.0438) Tregs was also observed. Data from this study demonstrates that targeting or developing therapies that specifically modulate Tregs number, trafficking, or activity, will be promising in NPC treatment.